Cutaneous manifestations of COVID-19 patients in a Hospital in São Paulo, Brazil, and global literature review - Silmara da Costa Pereira Cestari; Marcela da Costa Pereira Cestari; Gabriela Franco Marques; Ivana Lirio; Reinaldo Tovo; Ilana Cruz Silva Labriola (Sociedade Brasileira de Dermatologia, 2023)
Abstract Background: Since the beginning of the COVID-19 pandemic, a myriad of cutaneous manifestations have been described in association with this viral infection. However, in Latin America, this kind of data is still scarce. Objective: In this sense, the goal of this study was to describe the dermatological findings observed during SARS-CoV-2 infection, in a Brazilian Hospital. Methods: This is a cross-sectional, retrospective and descriptive study of 50 cases of new-onset dermatologic symptoms in patients with COVID-19, treated at Hospital Sírio-Libanês, from February to June 2020. Results: The patients (n = 50) were classified into 6 groups, according to the elementary lesions and the statistical analysis was performed. The most common cutaneous lesions were maculopapular eruptions (44%), necrosis, purpura, and livedo (32%), urticarial lesions (12%), pseudochilblains (4%) and papular-vesicular eruption (4%). In 46% of the patients the cutaneous lesions occurred in association with other symptoms, such as pruritus (38%), pain and burning sensation (8%). Lower limbs were affected in 44% of the cases, followed by the trunk (38%), upper limbs (24%) and face (14%). Cutaneous lesions were mostly found after other COVID-19 systemic symptoms, with a mean period between the viral syndrome and cutaneous signs of 5 days (SD = 6.1 days). Study limitations: It is a small sample, in a single-center study, with patients exclusively from a private Hospitals. Conclusions: Patients in Brazil have the same proportion of lesions as revealed in other studies in Europa. The compiled data is essential for a better understanding of cutaneous manifestations deemed secondary to COVID.